Features of modern monetary policy of the bank of Russia - A. V. Berdyshev (Вестник университета)
By the analysis of offi documents of the Bank of Russia, the features of modern monetary policy have been determined. It has been shown that in the context of a controversial decision on the Bank of Russia refusing to conduct currency interventions during the transition to the inflation targeting mode, as well as its focus on price stability, the monetary policy can`t be recognized as eff ctive because of its insubordination the goal to develop national production through increased lending to the real sector.